Gordian Knot – A Meckel’s Diverticulum: A Case Report - K, Biernat; M, Szymanski; A, Hellmann; R, Marszalek-Ratnicka; M, Sledzinski; M, Proczko-Stepaniak; L, Kaska (Archives of Clinical and Medical Case Reports, 2020)
Abstract not available in the source database.